Multi-agent application: a novel algorithm for hexapod robots gait transitions - A. K. M. Mohiuddin, Md. Yahya; Khan, Md. Raisuddin; Billah, Md. Masum; Farhana, Soheli (INSI Publications, 2010)
In this paper, a gait transition method has proposed that allows a group of multi-agent hexapod robot to switch from one gait to another gait with stable condition, during different terrain navigation. Typical gaits of locomotion are analyzed for hexapod robot. Hexapod robots frequently operate various gaits to locomote over a variety of surfaces. To enable locomotion in a changing surface, hexapod must be able to stably change between gaits while continuing to locomote. A comparative study, based on different gaits for different surface locomotion, concludes that the hexapod robot use two types gait for complex surfaces with concurrent gait transition during navigation. Finally, a gait transition algorithm is developed for hexapod robots in multi-agent application.